Are there really cooper pairs and persistent currents in aromatic molecules?. Issue 7 (4th February 2014) - Squire, Richard H.; March, Norman H.; Rubio, Angel
<x xml:space="preserve">Abstract</x> Over 20 years ago, one of us suggested the title was affirmative. In 2012, Cooper pairs were identified in several, but not all "aromatic" compounds tested, benzene being one. This manuscript discusses the formation of three time‐reversed pairs of states forming pseudobosons (high energy Cooper pairs) in benzene at room temperature. The large stabilization in energy that results is the additive effect of energy gaps of an s wave state and a charge density wave permitting the pseudobosons to exist at room temperature. The overall result of these interactions is three pseudobosons occupying the lowest boson state and the positions of the carbon nuclei are optimum by forming a perfect hexagon. The possibility of a persistent current exists; detection might not be easy. © 2014 Wiley Periodicals, Inc.